The literature review six steps to success - Machi, Lawrence A; McEvoy, Brenda T (Thousand Oaks, California Corwin, 2022)
"The fourth edition of the book adds new technology references, online guides, graphics, charts, and more to the six step model for successfully composing a literature review"--
Includes bibliographical references and index.
Keywords: Research -- Methodology -- Handbooks, manuals, etc; Research -- Methodology -- Study and teaching (Higher) -- Handbooks, manuals, etc; Research -- Methodology -- Study and teaching (Secondary) -- Handbooks, manuals, etc